2023
DOI: 10.21203/rs.3.rs-2685998/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone density of the cervical, thoracic and lumbar spine measured using Hounsfield units of computed tomography – results of 4350 vertebras

Abstract: Introduction The assessment of bone density has gained significance in recent years due to the aging population. Accurate assessment of bone density is crucial when deciding on the appropriate treatment plan for spinal stabilization surgery. The objective of this work was to determine the trabecular bone density values of the subaxial cervical, thoracic and lumbar spine using Hounsfield units. Material and Methods Data from 200 patients who underwent contrast-enhanced polytrauma computed tomography at a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Individuals within the normal BMI range (18.5-24.9) typically have better nutritional status and physical activity levels, which are bene cial for bone health. Studies indicate that these individuals are more likely to maintain adequate calcium and vitamin D intake, and moderate body weight exerts optimal pressure on bones, aiding in BMD maintenance [34] .Furthermore, the study observed a signi cant increase in thoracic spine BMD among females, potentially due to higher baseline thoracic BMD in males or differences in hormone levels, such as estrogen, which is known to signi cantly affect BMD in females [35] . Estrogen levels can in uence bone density, and healthy behaviors included in the LE8 score, such as physical activity and nutritional intake, may help maintain or increase estrogen levels, thereby enhancing BMD.The study did not nd a signi cant relationship between LE8 scores and head BMD [36] .…”
Section: Discussionmentioning
confidence: 75%
“…Individuals within the normal BMI range (18.5-24.9) typically have better nutritional status and physical activity levels, which are bene cial for bone health. Studies indicate that these individuals are more likely to maintain adequate calcium and vitamin D intake, and moderate body weight exerts optimal pressure on bones, aiding in BMD maintenance [34] .Furthermore, the study observed a signi cant increase in thoracic spine BMD among females, potentially due to higher baseline thoracic BMD in males or differences in hormone levels, such as estrogen, which is known to signi cantly affect BMD in females [35] . Estrogen levels can in uence bone density, and healthy behaviors included in the LE8 score, such as physical activity and nutritional intake, may help maintain or increase estrogen levels, thereby enhancing BMD.The study did not nd a signi cant relationship between LE8 scores and head BMD [36] .…”
Section: Discussionmentioning
confidence: 75%